Strengthening the Innovation Performance of Food SMEs Through Triple Helix Collaboration: Evidence from Regional Innovation Systems in Indonesia - Siti Arifah; Eny Boedy Orbawati; Catur Wulandari; Mumpuni Wahyudiarti Sitoresmi; Rochmat Aldy Purnomo (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Food Small and Medium Enterprises (SMEs) play a strategic role in Indonesia's regional economic development, yet many face limited innovation capacity, low technology adoption, and weak institutional collaboration. Within the Regional Innovation System (RIS), Triple Helix collaboration among government, academia, and industry is expected to strengthen SME innovation performance. This study examines the effects of government policy, academic support, government–academia collaboration, and innovation on food SME performance. A mixed-methods approach within a post-positivist paradigm was employed. Quantitative data were collected from 75 food SMEs in Magelang, Ponorogo, and Bandung Regencies and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Qualitative data from interviews, observations, and Focus Group Discussions were descriptively analyzed and integrated with quantitative findings. Government policy had a positive and significant effect on innovation performance (β = 0.275; p = 0.011), while academic support (β = 0.121; p = 0.101) and government–academia collaboration (β = 0.120; p = 0.155) showed positive but insignificant effects. Innovation was the strongest predictor (β = 0.380; p < 0.001), and the model explained 46.6% of the variance in innovation performance (R² = 0.466). Qualitative findings showed that government programs were the primary external driver, whereas university engagement and institutional coordination remained fragmented. Strengthening coordinated Triple Helix collaboration and innovation capacity is essential to enhance the competitiveness and sustainability of food SMEs.